Discovery and Biosynthesis of Novel Bioactive Microbial Natural Products - Wang, Lei; Justus Liebig University Giessen (My University, 2023)
Natural products derived from microorganisms like bacteria and fungi, are structurally diverse and represent a rich source for the discovery of new drugs to treat various human diseases, including infections and cancer. Many microorganisms derived bioactive compounds have been eventually developed into agents for clinical use. During our continuous research on bioactive secondary/specialized metabolites from microorganisms, the marine flavobacterium Tenacibaculum discolor sv11, the plant endophytic bacterium Pseudomonas brassicacearum Root401 and the fungus Palmiascoma qujingense ST006189 were investigated for their potential to produce specialized metabolites. Obligate marine flavobacteria of the genus Tenacibaculum play an important role in marine habitats. However, not much is known about natural products produced by these bacteria. T. discolor sv11 was chosen based on antimicrobial activity against B. subtilis. The P. brassicacearum Root401 genome indicated a high biosynthetic potential to produce specialized metabolites, especially for nonribosomal peptides (NRPs). The bacterium can cause disease in salt-stressed Arabidopsis thaliana. The extract of P. qujingense ST006189 contains a variety of chromone derivatives as revealed by LC-MS analysis. In this dissertation the focus was on the isolation and identification of bioactive secondary metabolites from the cultures of T. discolor sv11, P. brassicacearum Root401 and P. qujingense ST006189. Furthermore, the antimicrobial activity and virulence in A. thaliana, as well as the biosynthetic routes of these metabolites were tested and elucidated in this thesis. In summary, thirteen new alkaloids were isolated from T. discolor sv11. A novel sub group of cyclic lipopeptides was identified from P. brassicacearum Root401. Ten compounds were obtained from P. qujingense ST006189. The structures of the pure compounds were unambiguously elucidated on the basis of one- and two-dimensional NMR spectroscopy and mass spectrometry, together with Marfey’s analysis and X-ray crystallography. The pure compounds were investigated for their antimicrobial activity against bacteria and fungi. For selected compounds, their anthelmintic activity and virulence in plants was investigated. Putative biosynthetic gene clusters (BGCs), corresponding to the respective isolated compounds, were identified based on the bioinformatics analysis of the whole genome data, and the biosynthetic route was investigated using in vivo and in vitro experiments.
Keywords: 570; 630